Synthesis, characterization, and gas-sensing properties of alpha-Fe2O3 prepared from Fe3O4-alginate - Cuong, Nguyen Duc; Hoa, Tran Thai; Khieu, Dinh Quang; Tung, Truong Quy; Hieu, Nguyen Van (Vietnam Journal of Chemistry, 2014)
In this study, nanocomposite Fe3O4–alginate has been prepared by so-called two step method. The crystal structures and morphologies of as-synthesized nanopaticles (NPs) were characterized X-ray diffraction, and scanning electron microscopy. The surface states of Fe3O4-alginate NPs were characterized by Fourier transform infrared spectra. a-Fe2O3 was fabricated from the nanocomposite Fe3O4-alginate by heat treatment in air atmosphere at 600 oC and their gas sensing properties were investigated. The performance of the a-Fe2O3 in the detection of toxic and ﬂammable gases such as carbon oxide, ammonia, liqueﬁed petroleum gas, ethanol, and hydrogen was evaluated. The Fe2O3 based gas sensors exhibited high sensitivity and a response time of less than a minute to analytic gases. Keywords: Fe2O3, Fe3O4, gas sensor, alginate